IN BANGLADESH DIABETES STARTS EARLIER NOW THAN 10 YEARS BACK: A BIRDEM STUDY - Parvin Akter Khanam; Hajera Mahtab; Ashraf Uddin Ahmed; M. Abu Sayeed; A K Azad Khan; A K Azad Khan (IMC Journal of Medical Science, 2008)
BIRDEM is the largest referral center of diabetes in the world. It registered more than 300,000 diabetic patients from 1956 to 2005. This retrospective study compared the biophysical characteristics of diabetic patients registered in 1995 to those registered in 2005. Information on social (income, education), clinical (height, weight, blood pressure) and oral glucose tolerance (OGTT) of patients registered in 1995 and 2005 were retrieved from the BIRDEM registry. The age group ³ 20y was considered eligible. Overall, there were 11489 patients for 1995 and 19580 for 2005. Compared with the registry of 1995, a significant increase of registry for female patients were observed (39.5 vs. 46.7%, p<0.001) and also the rural population (31.9 vs. 47.4%, p<0.001). Likewise, the number of poor social class was also found higher in 2005 (5.2 vs. 25.5%, p<0.001). Young aged (<40y) registry was also significantly higher in 2005 (34.4 vs. 37.1%, p<0.001). Compared with the registered patients of 1995, adjusted for sex and area, those of 2005 had a significantly higher BMI, higher FPG and higher 2hPG (for all, p<0.001). In contrast, a significantly lower age, lower height and lower blood pressure were observed in those of 2005. We conclude that the age at registration for diabetes has decreased significantly in 2005 compared to that in 1995 indicating an earlier onset of diabetes. Significantly higher obesity in the year 2005 than 1995 indicates that there has been an increase in obesity that might be an important contributing factor for earlier onset of diabetes.